2017
DOI: 10.3382/ps/pex076
|View full text |Cite
|
Sign up to set email alerts
|

Transport-related stress and its resolution in turkey pullets: activation of a pro-inflammatory response in peripheral blood leukocytes

Abstract: The transportation process is one of the most stressful practices in poultry and livestock management. Extensive knowledge is available on the impact of transport on stress and animal welfare; however, little is known on the impact of transport on the physiology of turkey pullets, their welfare and health, and even less on the process of homeostatic recovery in the post-transport new environment. The main focus of this manuscript was to focus on trauma, stress, and recovery following transport of turkey pullet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 82 publications
1
9
0
1
Order By: Relevance
“…Our previous studies and those of others indicated an interaction between oxidative stress and the proinflammatory response ( Lee et al., 2019 , Wein et al., 2017a , Wein et al., 2017b ). Thus, restoration of homeostasis in broilers and turkeys in a state of oxidative stress (induced by transport) involved activation of an innate immune response.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…Our previous studies and those of others indicated an interaction between oxidative stress and the proinflammatory response ( Lee et al., 2019 , Wein et al., 2017a , Wein et al., 2017b ). Thus, restoration of homeostasis in broilers and turkeys in a state of oxidative stress (induced by transport) involved activation of an innate immune response.…”
Section: Introductionsupporting
confidence: 52%
“…Previously published observations by our group and others showed that stress induces upregulation of serum acute phase proteins, including lysozyme and transferrin and suggested that these acute phase proteins act as a means to restore homeostasis ( Cray et al., 2009 , Kim et al., 2011 , Yildiz and Altunay, 2011 , Najafi et al., 2016 , Wein et al., 2017a , Wein et al., 2017b ). Induced molting led to increased levels and mRNA of lysozyme and transferrin and thus support the previous observations.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…e isolates from the present study originated from turkey poults with yolk sacculitis (n � 15) and from the internal organs of subadult birds (n � 13). Commercially raised poults experience different stressors during the first week of life and might be more prone to enterococcal infections compared to subadult birds [70]. Consequently, one would expect that Enterococcus infections in subadult turkeys are caused by virulent strains and by predominant species in poultry disease such as E. faecalis.…”
Section: Discussionmentioning
confidence: 99%